2020
DOI: 10.1016/j.colsurfa.2019.124189
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-free and hydrophobic hexadecyltrimethoxysilane-TiO2 coated mesh for gravity-driven oil/water separation

Abstract: Superhydrophobic and superoleophilic meshes have attracted great attention in oil/water separating application. However, superhydrophobic surfaces are not only complicated in preparation but also easy to break in practical applications. In this paper, we prepared fluorine-free hydrophobic hexadecyltrimethoxysilane (HDTMS)-TiO2 coated meshes with properties of cost-effectiveness, easy to manufacture, and high separation efficiency by a liquid phase deposition method. The surface topography, composition, and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…The WCA decreased by about 10 compared with that before soaking, which may be due to the fact that part of HDS was dissolved in the organic solvents, which increased the surface energy of the fabric and destroyed the superhydrophobic property. 54,55 It can be seen from the stability test results that the prepared superhydrophobic PET fabric has excellent resistance to washing, abrasion, UV irradiation, sea water, acid/alkali and organic reagents, which provides basis for its application in oil/water separation.…”
Section: Stability Tests Of the Pda/fe/hds Pet Fabricmentioning
confidence: 99%
See 1 more Smart Citation
“…The WCA decreased by about 10 compared with that before soaking, which may be due to the fact that part of HDS was dissolved in the organic solvents, which increased the surface energy of the fabric and destroyed the superhydrophobic property. 54,55 It can be seen from the stability test results that the prepared superhydrophobic PET fabric has excellent resistance to washing, abrasion, UV irradiation, sea water, acid/alkali and organic reagents, which provides basis for its application in oil/water separation.…”
Section: Stability Tests Of the Pda/fe/hds Pet Fabricmentioning
confidence: 99%
“…The -O]C-O vibration absorption bands of aromatic esters appear at 1245 cm À1 and 1094 cm À1 , and the peak at 1016 cm À1 (ref 47[48][49][50],. indicating that the long-chain alkyl groups were successfully introduced to the surface of PET.Fig.…”
mentioning
confidence: 99%
“…A number of variables, including the characteristics and volume of silanes and the distribution and size of TiO 2 NPs, may affect the efficacy of the treatment method and the exterior physiochemical properties of modified TiO 2 NPs. To date, various silanes have been employed to modify TiO 2 NPs including hexadecyltrimethoxysilane [34], (3-glycidoxypropyl)trimethoxylsilane [26], 3-(triethoxysilyl)propyl isocyanate [35], octadecyltrimethoxysilane [36], 3-methacryloxypropyltrimethoxysilane [37], vinyltrimethoxysilane [38], bis(3-triethoxysilylpropyl)tetrasulfide [39], and (3-aminopropyl)trimethoxysilane [40], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that TiO 2 -based superhydrophobic suspensions represent a viable means of external surface cleaning coatings (via a self-cleaning method) [34,[41][42][43]. Lu et al [44] discussed the use of a highly adaptable ethanolic suspension of perfluorooctyltriethoxysilane-coated dual-sized TiO 2 NPs, which achieved definite self-cleaning and preserved superhydrophobicity even after immersion in oil.…”
Section: Introductionmentioning
confidence: 99%
“…Oil spills can cause severe health and environmental impacts and enormous economic losses [ 1 ]. Oil spills in water may cause oxygen deficiency in aquatic systems, leading to the death of living organisms [ 2 ]. The separation of oil-related contaminants from water has received significant importance due to their substantial adverse impact on the economy and the environment.…”
Section: Introductionmentioning
confidence: 99%